Comprehensive Bioinformatics Analysis of Key Methyltransferases and Demethylases for Histone Lysines in Hepatocellular Carcinoma. (22nd December 2020) - Zheng, Yang; Tang, Lili; Chen, Guojiang; Liu, Ziling
Background & Aims: Methylation of lysines on histones, controlled by various methyltransferases and demethylases, is an important component of epigenetic modifications, and abnormal regulation of such enzymes serves as common events in hepatocellular carcinoma. We determined to identify important methyltransferases and demethylases that might regulate the development of hepatocellular carcinoma by bioinformatics. Methods: The Oncomine and UALCAN databases were used to retrieve mRNA expression levels of histone lysine methyltransferases and demethylases in hepatocellular carcinoma. Data analyses of genetic alterations, mainly mutations and copy number alterations, were performed on the cBioportal platform. Protein-protein interactions were established in the STRING database. Results: mRNA expression of 8 genes correlated with clinical staging and grading, whereas 4 genes indicated a role in the prognosis, all co-expressed with SEDB1 and WHSC1. Genetically, 12 genes showing an alteration rate higher than 5% were identified, and only 3 were indicative of prognosis. Copy number gains in ASH1L, SETDB1, and KDM5B might partially contribute to the upregulation of their mRNA expression. The close relationship of mutations in MLL2/MLL3 with driver gene mutations in hepatocellular carcinoma provided a rationale for further investigation. Conclusions: We identified 11 methyltransferases and demethylases for major histone lysines that might be promising research targets in the pathogenesis, development, and prediction of prognosis in hepatocellular carcinoma using bioinformatics.